SASI - BASED PROTECTION FOREST STRATEGY IN MALUKU (AMBON) - Tehupeiory, Aarce (International Journal of Research -GRANTHAALAYAH, 2021)
This research is about Sasi-based protection forest strategy, it is done to find out how the Sasi-based protection strategy mechanism in protecting the forest. The research method used is a qualitative research method with a normative legal research. The research was conducted at Universitas Kristen Indonesia from January to March 2021. The objects studied in this study were documents either in reports or regulations related to indigenous peoples’ local wisdom. The research instrument used was a document checklist. The data analysis technique used is the descriptive analysis technique. The result of the research is that traditional Sasi wisdom has values and norms to protect forests, water sources, annual plants and food plants. With the concept and understanding of how environmental managers with various customary rules to obtain benefits and maintain the kinship value of area units that already have an identity and must continuously be maintained in the aftermath of the COVID-19 pandemic. Besides, food security for indigenous peoples on the island of Maluku (Ambon) during the Covid-19 pandemic, namely by building food security by encouraging a new paradigm based on local food with directions and policies for developing food security and absorption of dryland technology to support sustainable food self-sufficiency through sources